Trajectories of and Risk Factors for University Students’ Emotional Well-Being and Distress Across the Academic Year - Fang, Shichen; Barker, Erin; Arasaratnam, Gaya; Lane, Victoria; Doucerain, Marina M.; Tuong Nguyen, Cat; O'Connor, Roisin; Panaccio, Alexandra; Rabinovich, Debora (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
In recent years, post-secondary students’ mental health has become an important public health concern. Guided by the dual-factor model of mental health, this study examined average mental health fluctuations and associations with a comprehensive list of pre-existing risk factors in Canadian undergraduates (N = 1,004, 61% women, 36% visible minority) followed 16 times throughout the 2020/2021 academic year during the COVID-19 pandemic. We used piecewise latent growth curve modelling to specify patterns of emotional well-being (positive affect) and distress (depressive and anxiety symptoms) across the year. We also examined stressful life experience and sociodemographic risk factors as predictors of baseline levels of emotional well-being and distress in September. Mental health declined in the first half of each semester, remained stable until the end of each semester, and improved over the winter break. Mental health history, past and recent stressful life experiences, age, gender, sexual orientation, visible minority status, subjective social status, and current financial strain predicted baseline mental health at the start of the academic year. This study offers novel insights into patterns of change in students’ mental health and associated risks important for campus programming and intervention efforts.